How authoritarian rulers seek to legitimize repression: framing mass killings in Egypt and Uzbekistan - Edel, Mirjam; Josua, Maria (2018)
Abstract: How do authoritarian rulers legitimate repressive actions against their own citizens? Although most research depicts repression and legitimation as opposed strategies of political rule, justified coercion against some groups may generate legitimacy in the eyes of other parts of the population. Building upon this suggested link between legitimation and repression, this article studies the justifications of mass killings. To this end, framing theory is combined with recent research on the domestic and international dimensions of authoritarian rule. We contend that frames are directed towards specific audiences at home and abroad. Moreover, given the common threats at the global level and the diffusion of repressive tactics, we assume that learning processes influence discursive justifications of repression in authoritarian regimes. We provide an analysis of government rhetoric by comparing the protest crackdowns of Rabi'a 'Adawiya Square in Egypt and Fergana Valley in Uzbekistan, tak